A psychoanalytic view of trauma in the coronavirus pandemic - Juliane da Silva Pessoa; Marise de Leão Ramôa (Estudos de Psicologia (Campinas))
Abstract Objective This article seeks to understand the origin of trauma related to the Covid-19 pandemic. Method To achieve this objective, an integrative literature review was conducted, providing a comprehensive, systematic, critical, and reflective analysis. Results The research results reveal that the experience of trauma is unique to each individual, with behaviors ranging from helplessness to denial. Helplessness, marked by uncertainty and hopelessness, engenders feelings of anguish associated with the widespread death and illness in the population. On the other hand, denial, functioning as a psychological defense mechanism, represents the return of the repressed, manifesting as an experience of rejecting castration. Conclusion This reveals a narcissistic individualism, symbolized by the desire not to succumb to social isolation or adhere to health protocols. Instead, individuals choose to live a life governed by the pleasure principle, often at the expense of collective well-being.